Archaeology's visual culture - Balm, Roger, 1947-, author.
1 online resource (xii, 286 pages)
Keywords: "Archaeology's Visual Culture explores archaeology through the lens of visual culture theory. The insistent visuality of archaeology is a key stimulus for the imaginative and creative interpretation of our encounters with the past, acknowledging the multiplicity of meanings that cohere around artifacts, archaeological sites and museum displays. Archaeology's Visual Culture investigates the nature of this projection, revealing an embedded subjectivity in the imagery of archaeology. Using a wide range of case studies the book highlights the way archaeologists view objects and the consequences that ensue from ways of seeing"--Provided by publisher.